2015
DOI: 10.1177/1545968315597072
|View full text |Cite
|
Sign up to set email alerts
|

Rehabilitation Interventions for Improving Social Participation After Stroke

Abstract: Background-Despite the fact that social participation is considered a pivotal outcome of a successful recovery after stroke, there has been little attention on the impact of activities and services on this important domain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
49
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(56 citation statements)
references
References 56 publications
(207 reference statements)
1
49
0
4
Order By: Relevance
“…The same study showed that the participation domain was also one of two domains (SIS) with most reported problems at both 3 and 12 months post-stroke. 22 Several other studies 32,[34][35][36] have also confirmed relationships between physical activity or ADL performance and participation, 6 months or longer after stroke.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…The same study showed that the participation domain was also one of two domains (SIS) with most reported problems at both 3 and 12 months post-stroke. 22 Several other studies 32,[34][35][36] have also confirmed relationships between physical activity or ADL performance and participation, 6 months or longer after stroke.…”
Section: Discussionmentioning
confidence: 73%
“…Univariate logistic regressions were performed to evaluate relationships between the level of participation and plausible predictive variables that were chosen in accordance with previous research. 3,19,20,32 Age, sex, NIHSS at baseline, living alone or not, and functions from the SIS, composite Physical, Memory and Thinking, Emotions, and Communication, were independently evaluated with the participation level, the threshold set at P≤.25.…”
Section: Data Handling and Analysismentioning
confidence: 99%
“…Social isolation is amenable to change and a meta-analysis found that activities which encouraged individuals to leave the house and interact with others, as well as exercise activities could improve social participation. 17 Addressing social isolation in the future with implementation research meets this consumer identified need.…”
Section: Discussionmentioning
confidence: 99%
“…El conocimiento sobre las intervenciones que promueven los mejores resultados en esta recuperación puede ayudar a optimizar los servicios de atención de salud. La recuperación exitosa de un accidente cerebrovascular debe resultar en una mejor calidad de vida y mayor grado de participación en la comunidad similar a la que tenía previamente a la lesión (Obembe & Eng, 2016). La participación social es, por tanto, uno de los objetivos más importantes de la rehabilitación de pacientes con DCA y se sitúa generalmente en el último lugar (Obembe & Eng, 2016).…”
unclassified
“…La recuperación exitosa de un accidente cerebrovascular debe resultar en una mejor calidad de vida y mayor grado de participación en la comunidad similar a la que tenía previamente a la lesión (Obembe & Eng, 2016). La participación social es, por tanto, uno de los objetivos más importantes de la rehabilitación de pacientes con DCA y se sitúa generalmente en el último lugar (Obembe & Eng, 2016). No obstante muchas son las investigaciones que estudian cuáles deberían ser los objetivos principales de la rehabilitación del daño cerebral, aunque no parece existir un acuerdo claro.…”
unclassified